Formulation of larvicidal granules using the ethanolic extract of Capsicum frutescens (Linn.) fruits - Argonza, Femina Grace M.; Claros, Christine D.; Soria, Marie Claire A.
To combat the dangers of mosquito borne disease from common vectors such as Aedes aegypti, different methods of vector control have been employed. The most common of which is through synthetic insecticides that target adult mosquitoes. However, these are found inefficient as this method target only the adult and does not include eggs or larva which will eventually emerge into mosquitoes. Also, there is already a rising incidence of mosquito resistance to synthetic chemical insecticides at present. Hence, developing a natural larvicidal agent is necessary to combat mosquito vectors more effectively. In this study, the crude ethanolic extract of Capsicum frutescens fruit was used in the formulation of larvicidal granules. The crude extract resulted in 100% mortality after 24 hours of exposure and is significantly different (p < 0.0001) with the positive control. Stability testing of the crude extract and compatibility testing of the different extract- excipient mixtures was conducted prior to the trial formulations of the granules. The formulated granules were assessed through quality control tests and larvicidal activity bioassay. The chosen formulation resulted in 100% mortality within 24 hours of exposure which is significantly different (p < 0.0001) with the positive control. The dose response bioassay of the formulation showed LC 50 and LC 90 0f 108.68 and 233.44 ppm respectively for 24-hr exposure and 102.68 and 182.50 ppm for 48-hr exposure. In conclusion, the study allowed the satisfactory formulation of larvicidal granules against Aedes aegypti. Thus, it could contribute significantly to alternative integrative practices of vector management.